Development of cryopreservation for Loxocarya cinerea: An endemic Australian plant species important for post-mining restoration - Kaczmarczyk, Anja; Funnekotter, Bryn; Turner, S.; Bunn, E.; Bryant, G.; Hunt, T.; Mancera, Ricardo (CryoLetters, 2013)
We report the development of a cryopreservation protocol for the endemic Western Australian plant species Loxocarya cinerea (Restionaceae). Shoot tips from two genotypes, SXH404 and SXH804, were cryopreserved using the droplet-vitrification technique. Control explants, which were cryoprotected, but not cooled, showed regeneration for both genotypes (SXH404, 22.1 ± 5.9%; SXH804, 67.7 ± 9.6%). Extension of incubation in PVS2 from 30 to 60 min did not lead to survival after cryopreservation. Thermal analysis using differential scanning calorimetry confirmed the beneficial effect of a loading phase but also revealed no or very little ice formation after cryoprotection of shoot tips in other treatments. Regeneration following cryopreservation was obtained for genotype SXH804 (4.3 ± 2.1%) but not for SXH404. Regenerated explants of L. cinerea SXH804 were morphologically identical to tissue-cultured plants. As an alternative to shoot tips, callus tissues of clone SXH404 were successfully cryopreserved (>66.7% post LN survival) using the same protocol.